Research of the Vacancy Migration Process on the Surface of BC Nanolayer - S.V. Boroznin; I.V. Zaporotskova; N.P. Boroznina (Журнал нано- та електронної фізики)
The ionic conductivity and structure in which it cans be realized research is very important for the development of modern batteries. Using of new materials will enable from such deficiencies as little time of life, small energy, and possibility of leak from battery. In this paper we present the results of investigation of ionic conductivity process of boron carbon nanolayers. The research was performed using the MNDO method within the framework of a molecular cluster model and DFT method using B3LYP functional and 6-31G basis. For investigation of ionic conductivity processes the vacancy formation on the nanolayer have been modeled. Energetic and electronic characteristics of these processes have been carried out. The vacancy migration process has been modeled. The conductivity coefficient dependence of temperature has been found.